Implications of hydraulic anisotropy in periglacial cover beds for flood simulation in low mountain ranges (Ore Mountains, Germany) - Reinhardt-Imjela, Christian; Maerker, Katja; Schulte, Achim; Kleber, Arno (DIE ERDE – Journal of the Geographical Society of Berlin, 2018)
The simulation of floods with conceptual rainfall-runoff models is a frequently used method for various applications in flood risk management. In mountain areas, the identification of the optimum model parameters during the calibration is often difficult because of the complexity and variability of catchment properties and hydrological processes. Central European mountain ranges are typically covered by Pleistocene periglacial slope deposits. The hydraulic conductivity of the cover beds shows a high degree of anisotropy, so it is important to understand the role of this effect in flood models of mesoscale mountain watersheds. Based on previous field work, the study analyses the sensitivity of the NASIM modeling system to a variation of vertical and lateral hydraulic conductivity for the Upper Flöha watershed (Ore Mountains, Germany). Depending on the objective function (Nash-Sutcliffe coefficient, peak discharge), two diametric parameter sets were identified both resulting in a high goodness-of-fit for total discharge of the flood events, but only one reflects the hydrological process knowledge. In a second step, the knowledge of the spatial distribution of the cover beds is used to investigate the potential for a simplification of the model parameterisation. The soil types commonly used for the spatial discretisation of rainfall-runoff models were aggregated to one main class (periglacial cover beds only). With such a simplified model, the total flood discharge and the runoff components were simulated with the same goodness of fit as with the original model. In general, the results point out that the anisotropy in the unsaturated zone, which is intensified by periglacial cover beds, is an important element of flood models. First, a parameter set corresponding to the hydraulic anisotropy in the cover beds is essential for the optimum reproduction of the flood dynamics. Second, a discretisation of soil types is not necessarily required for flood modeling in Central European mountain areas.